Management problems in patients with pancreatic cancer from a surgeon's perspective - Klose, Johannes; Ronellenfitsch, Ulrich; Kleeff, Jörg H. (Seminars in oncology, 2021)
Pancreatic cancer, Surgery, Palliative treatment